Effectiveness of Group Guidance on Modeling Techniques to Increase the Learning Independence - Raini Retno Wulansari; Nur Azizah; Agus Basuki (Postgraduate, University of Mataram, 2023)
Education is an effort to improve the quality of human life through developing their potential. one of which is that students have the ability to learn independently. In fact, taking initiative and depending on others is a problem that often occurs among students. The aim of this research is to determine the effectiveness of modeling technique group guidance to increase the learning independence of class VII students at SMP N 1 Padamara. This type of research is quantitative research with experimental methods. This research design is one group pretest and posttest. The population of this research was 50 students and the sample was 8 students. Research analysis used the Wilcoxon test with the help of SPSS 26 for Windows. Based on the results of this research, it shows an increase in learning independence after following the modeling technique group guidance services provided. This is shown in the average pre-test score of 53.2 and post-test average score of 95.4. Based on the results of the Wilcoxon test using SPSS 26, the Z count in the experimental class was -2.521 and a significance level of 0.05. It is known that the Asymp.Sig.(2-tailed) value is 0.012<0.05, so Ho is rejected and Ha is accepted. The conclusion of this research is that modeling technique group guidance services are effective in increasing the learning independence of class VII students at SMP N 1 Padamara